Going Concern Audit Opinions From the Perspective of Audit Characteristics (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study examines the impact of audit lag, audit quality, prior audit opinion, opinion shopping, and audit client tenure on the going concern audit opinion of Consumer & Cyclical sector companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023. A going concern audit opinion reflects the auditor's concerns about a company's ability to sustain operations in the future. The population consists of 163 companies, with 103 selected through purposive sampling, resulting in 309 data points over three years. This quantitative research relies on secondary data from independent audit reports available on the IDX. Logistic regression analysis, performed using SPSS 23.0, reveals that audit quality significantly and negatively influences the likelihood of a going concern audit opinion and prior audit opinions have a significant positive impact. Conversely, audit lag, opinion shopping, and audit client tenure do not significantly affect going concern audit opinions. These findings provide insights for auditors, regulators, and stakeholders regarding factors that influence auditors’ assessments of a company’s financial stability in the Consumer & Cyclical sector.